One new species of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Guizhou Province, China - Pan, Yangyang; Bian, Xun (Zootaxa, 2023)
Phlugiolopsis was proposed by Zeuner in 1940 with Phlugiolopsis henryi Zeuner, 1940. Chinese scholars Xia & Liu first studied the genus in 1993 and described three new species from Wuling Mountains Area of Southwestern China, among which Phlugiolopsis brevis Xia & Liu, 1993 and Phlugiolopsis tuberculata Xia & Li, 1993 were mainly distributed in Guizhou Province. Twenty years later, Bian et al. (2013) described the third species of Phlugiolopsis from Guizhou, namely Phlugiolopsis xinanensis Bian, Shi & Chang, 2013. Compared with Yunnan Province, the classification of Phlugiolopsis in Guizhou is far from sufficient. Herein based on new specimens deposited in Guangxi Normal University, we describe one new species from Guizhou, China.